PERANCANGAN MESIN EKSTRUSI UNTUK DAUR ULANG SAMPAH PLASTIK BERBENTUK SILINDER - Budhi Martana; Sigit Pradana; Muhammad Arifudin Lukmana (Politeknik Negeri Jakarta, 2020)
Extrusion technology is one way that can be done to produce a product. The extruder machine is a tool that is quite simple but has its own uniqueness, the way this tool works is to insert raw materials which will be processed and then pushed out through a die in accordance with the desired shape. The purpose of this research is to design an extruder in order to produce a cylindrical product (filament), and to recycle waste into a product that has added value and economic value, so that it can be applied to society as an effort to reduce plastic waste. The research method used is development research with the determination of several variables, namely: control variables in the form of plastic material with the type of PET and HDPE, the independent variables are temperature and engine speed (rpm), and the dependent variable is the time needed to produce a product. The results obtained for the PET type plastic have the characteristics of fast liquid and runny, the results are discontinuous (discontinuous), brittle (brittle), for HDPE it has the characteristics of liquid and hard, continuous yield, the resulting surface looks rough with flexible plastic properties, strong and elastic, while for the mixture of PET and white HDPE, the characteristics are liquid, and continuous. This mixture of PET and HDPE has a long drying time of up to 1350 seconds.